2004
DOI: 10.1021/bi035847x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Inhibitory Activity of oatp Antisense Oligonucleotides by Incorporation of 2‘-O,4‘-C-Ethylene-Bridged Nucleic Acids (ENA) without a Loss of Subtype Selectivity

Abstract: Antisense oligonucleotides (AONs) that specifically target the genes of rat organic anion transporting polypeptide (oatp) subtypes were selected by using antisense in vitro selection (AIVS) and a conventional gene alignment program (GAP). When we incorporated several of our original 2'-O,4'-C-ethylene-bridged nucleic acid (ENA) residues into AONs, which were designed as gapmers containing a series of 2'-deoxynucleotides in the center, at both the 3' and 5' ends, the inhibitory activity of these oatp AONs was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…We have confirmed the intracellular antisense activity of ENA oligonucleotides against organic anion transporting polypeptide (oatp). [10] The ENA oligonucleotides also exhibit excellent triplex formation with dsDNA. [11] They could be used for exon skipping to bind dystrophin pre-mRNA and inhibit its splicing reaction.…”
Section: Introductionmentioning
confidence: 99%
“…We have confirmed the intracellular antisense activity of ENA oligonucleotides against organic anion transporting polypeptide (oatp). [10] The ENA oligonucleotides also exhibit excellent triplex formation with dsDNA. [11] They could be used for exon skipping to bind dystrophin pre-mRNA and inhibit its splicing reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that fully modified ASOs (i.e., with 2 0 ribose modifications at all nucleotide positions) act predominantly by inhibiting mRNA translation [Crooke, 1999;Fulford et al, 2000]. However, modified ASOs with six to eight DNA bases in the center lacking ribose modification at the 2 0 position (known as ''GAPmers'') efficiently activate RNase H to degrade the target mRNA Zamaratski et al, 2001;ten Asbroek et al, 2002]. Like unmodified and fully modified ASOs, GAPmers form stable duplexes with target mRNA, although the stability is decreased with increasing length of the alkyl chain and with an increasing number of modified nucleotides in a sequence.…”
Section: Asr Chemistries Aso Chemistrymentioning
confidence: 99%
“…17,19,20) ENA-DNA-ENA gapmer-designed oligonucleotides that can undergo RNase H-mediated degradation are used as AONs. When ENA-modified AONs against vascular endothelial growth factor (VEGF) mRNA were introduced into human cancer A549 cells in the presence of a cationic polymer, more than 90% inhibition of VEGF mRNA production was observed after RT-PCR analysis.…”
Section: Application Of Ena Oligonucleotides As Antisense Moleculesmentioning
confidence: 99%
“…19,20) When several ENA residues were incorporated into AONs, the inhibitory activity of these oatp AONs was enhanced. Moreover, these ENA AONs did not lose their oatp-subtype selectivity.…”
Section: Application Of Ena Oligonucleotides As Antisense Moleculesmentioning
confidence: 99%